Sonochemical Preparation of Nano-TiO2 and Photocatalytic Degradation of Methylene Blue - Wang, Hongbin; Zhang, Shili; Liu, Manhong; Liu, Tiancheng; Yang, Min (Asian Journal of Chemistry, 2012)
This paper reports the preparation of nano-TiO2 powder by ultrasound hydrolyzed titanium(IV) chloride and methylene blue were used to photocatalysis degradation. We studied the respond time, pH value, the amount used and the light distance, etc. We also studied the factors affecting the degradation rate of methylene blue and compared the P-25 and TiO2 power. Experiments show that the photocatalytic activity of TiO2 is better. The respond time is 150 min, the catalyst dosage is 0.2000 g, the light distance is 16 cm. When pH value is between 6-8, the degradation rate is up to 99.35 %.